Iniciação profissional docente: um estudo a partir da produção acadêmico-científica brasileira (2015-2019) - Gonçalves, Natália Marques (2022)
Teacher induction is a training strategy used as a link between initial and continuing education, which allows a management team to welcome and accompany beginning teachers during the first years of the teacher professional development cycle. Given this scenario, this research aims to point out and analyze the main contributions of Brazilian academic-scientific productions for understanding the reality of the professional insertion of Basic Education teachers, present in master's dissertations and doctoral theses in graduate programs teaching and education published and defended in the period from 2015 to 2019, validated by the Coordination for the Improvement of Higher Education Personnel (Capes) of Postgraduate Programs with concept 4, 5, 6 or 7, Ciao the insertion of initiation programs to teaching that can assist in the entry of beginning teachers into the teaching career, the methodology adopted in this research is based on the assumptions of qualitative research, using the State of the Art as a tool, which investigates, catalogs and understands the current scenario of professional insertion in education. basic. The analysis of academic productions was based on the following guiding principles: (1) Composition of the research scenario; (2) Guiding principles of teacher education. The educational product elaborated in this dissertation emerged through initiatives, readings, discussions, studies and reflections on teacher education and the training strategy of Teacher Induction. The development of the educational product took place in two stages: (1) a training project entitled Teaching Induction: a training strategy for beginning teachers, aiming to train managers for implementation in the school institution in which they are manager; (2) investigative form with managers, which was divided into two stages: (a) identification and profile of managers; (b) reading and reflection on the training project, as well as contributions to the possible development in the school institution in which they act as managers. The investigation developed in this dissertation allows us to conclude that there is a need for specific training for managers, so that they develop skills and competences for pedagogical and administrative work relevant to their function, the importance of work among peers for mutual development from the teaching staff and the school institution, the need to implement public policies to encourage teaching, in the first years of professional development, such as teaching induction.